Maqālāt-i Mumtāz - Hasan, Mumtaz; Ḥaqqī, Shānulḥaq, 1917-2005. (Karācī : Idārah-yi Yādgār-i G̲ẖālib, 1995)
Collection of articles on Urdu literature, education, culture and on Sir Muhammad Iqbal, 1877-1938, national poet of Pakistan.
Includes bibliographical references.
Mode of access: Internet.
In Urdu.
Keywords: Iqbal, Muhammad, -- Sir, -- 1877-1938 -- Criticism and interpretation; Urdu literature -- History and criticism; Pakistan -- Civilization